2011
DOI: 10.1016/j.neuroimage.2010.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Impaired error-likelihood prediction in medial prefrontal cortex in schizophrenia

Abstract: The cognitive impairment in individuals with schizophrenia includes deficits of working memory in dorsolateral prefrontal cortex and deficits of performance monitoring in medial prefrontal cortex (MPFC). Recent work suggests a more general role for MPFC in predicting the outcome of actions and then evaluating those predictions. Here we investigate, in individuals with schizophrenia, two specific effects associated with this role: the error likelihood effect (occurring on trials with correct performance, but fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
3
20
1
Order By: Relevance
“…There was also evidence of overall increased signaling to high risk/reward 'Success' outcomes in caudal ACC and increased signaling to low risk/reward 'Explode' outcomes in IFG and caudal ACC from baseline to follow-up. These results may be consistent with an increased surprise signal to unexpected outcomes (i.e., high risk successes and low risk explosions) in recovery which may, in turn, reflect formation of stronger expectancies based on previous outcomes (Alexander and Brown, 2010, 2011, 2014; Krawitz et al, 2011). However, we cannot exclude the possibility that this is a learning effect, unrelated to substance use recovery.…”
Section: Discussionsupporting
confidence: 62%
“…There was also evidence of overall increased signaling to high risk/reward 'Success' outcomes in caudal ACC and increased signaling to low risk/reward 'Explode' outcomes in IFG and caudal ACC from baseline to follow-up. These results may be consistent with an increased surprise signal to unexpected outcomes (i.e., high risk successes and low risk explosions) in recovery which may, in turn, reflect formation of stronger expectancies based on previous outcomes (Alexander and Brown, 2010, 2011, 2014; Krawitz et al, 2011). However, we cannot exclude the possibility that this is a learning effect, unrelated to substance use recovery.…”
Section: Discussionsupporting
confidence: 62%
“…A similar argument based on a deficit in a neural comparator linking perception and action impairment has been made to extend this concept into cognitive systems to explain impaired theory of mind and emotional response deficits (Frith et al, 2000; Jeannerod, 2003). Indeed, a recent study has reported evidence for a deficit in error-likelihood prediction in the mPFC in schizophrenia patients in the context of a working-memory task (Krawitz et al, 2011). Additional behavioral evidence for breakdown of a comparator mechanism linking perception and action during self-other interactions is impaired gesture and movement imitation (Matthews et al, 2013) and emotional contagion (unconscious imitation of smiling and yawning – Haker and Rössler, 2009) in patients.…”
Section: Self-processing In Schizophreniamentioning
confidence: 99%
“…The current evidence of regional distinctions within the ACC suggests that these two signals may not only exist within ACC but also be spatially distinct. For example, several recent studies have outlined distinct subregions of the ACC based on probabilistic connectivity (Beckmann et al, 2009), dynamic causal modeling (Fan et al, 2008), motor representations (Amiez and Petrides, 2012), neural deficits in schizophrenia (Krawitz et al, 2011), and experimental paradigms incorporating error, conflict, and task-switching effects into a single design (Nee et al, 2011), highlighting the anatomical and functional heterogeneity of the ACC. The current study was designed to test whether a model-based analysis could identify these prediction and outcome processes in the ACC, and if so, whether these processes are spatially distinct or overlapping.…”
Section: Introductionmentioning
confidence: 99%